2012
DOI: 10.1189/jlb.1011518
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1 in T cells ameliorated dextran sodium sulfate-induced murine colitis

Abstract: HIF-1 is active in hypoxia, such as inflamed mucosa, and HIF-1 in epithelium has been reported to control inflamed mucosa in IBD models. Although T cells play an important role for pathogenesis of IBD, the function of HIF-1 in T cells remains to be elucidated. We aimed to clarify the function of HIF-1 in T cells in IBD with focus on the balance between Treg and Teff. Double immunohistochemistry of colonic mucosa in IBD patients showed that HIF-1 was expressed in T cells infiltrating the inflamed mucosa, sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
60
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 37 publications
11
60
0
Order By: Relevance
“…Our observations are in agreement with previous reports showing decreased IFN-g secretion by TCR-triggered T cells in vitro in hypoxic conditions (1,15,16), as well as more severe colonic inflammation (16) and increased antibacterial effect in HIF-1a-deficient mice in a murine model of sepsis (1).…”
Section: Hif-1 Negatively Regulates Th1 Priming In Vivosupporting
confidence: 83%
“…Our observations are in agreement with previous reports showing decreased IFN-g secretion by TCR-triggered T cells in vitro in hypoxic conditions (1,15,16), as well as more severe colonic inflammation (16) and increased antibacterial effect in HIF-1a-deficient mice in a murine model of sepsis (1).…”
Section: Hif-1 Negatively Regulates Th1 Priming In Vivosupporting
confidence: 83%
“…It has been reported that HIF-1 in T cells ameliorates DSSinduced colitis by controlling the balance of Tregs and T effector cells. 34 Treg-intrinsic HIF-1a is further required for an optimal Treg function to control colitis. 12 We now focused on the role of HIF-1a in DCs because they play a crucial role in regulating the immune response and are also involved in the pathogenesis of IBD.…”
Section: Hif Plays a Crucial Role In The Regulation Of Many Immune Cementioning
confidence: 99%
“…However, the use of a PHD inhibitor (FG-4497), which stabilizes HIF-1a, had a beneficial influence on weight loss, histological modifications and TNF-a production in a murine model of TNBS-induced colitis (21) . T-cells that infiltrated the inflamed mucosa in IBD patients expressed more HIF-1a, and HIF-1a KO mice displayed more severe DSS-induced colonic inflammation (12) . Based on these positive reports, PHD inhibitors have been suggested for use as a potential therapeutic approach to treat IBD patients (7) .…”
Section: Discussionmentioning
confidence: 99%